A distribuição de Chironomidae (Diptera) e Oligochaeta (Annelida, Clitellata) é similar em um rio e área fluvial lateral? - Cesar, Daniela Aparecida Silveira [UNESP]; Henry, Raoul [UNESP] (FapUNIFESP (SciELO), 2017)
Numerous factors may affect the pattern of distribution of benthic fauna in a river mouth region and, among the macroinvertebrates, Chironomidae and Oligochaeta are the most abundant groups and most tolerant to environmental changes. Aim: The aim of this study was to evaluate the controlling factors of and a possible similarity between Chironomidae and Oligochaeta assemblies at two close sites, the mouth of the Guareí River into the Paranapanema River (São Paulo, Brazil) and its lateral fluvial area. Methods: Fauna samples were collected every three months during one year. Water physical and chemical variables and sediment variables were also determined in the same period. Results: Both assemblies presented low density variability over time in the lateral area due to sediment characteristics and environmental factors. Taxa Caladomyia, Parachironomus, Pristina sp., Pristina osborni, Bothrioneurum and Opistocysta funiculus were recorded at this site. The Guareí River presented both greater temporal and spatial variations, attributed mainly to a reduction in the water level. Greater organism abundance, especially of Chironomus and Tubificinae, was observed in the river. Conclusions: Dissimilarity in temporal and spatial distributions of Chironomidae and Oligochaeta was attributed to peculiar characteristics of the two study sites, a river channel and a lateral area. Reduction in the water level over the year was the main controlling factor of Chironomidae and Oligochaeta richness and density in the river. In the lateral area, the presence and abundance of certain taxa were determined by the nature of the sediment and water physical and chemical variables.
Is similar the distribution of Chironomidae (Diptera) and Oligochaeta (Annelida, Clitellata) in a river and a lateral fluvial area?
Keywords: Macroinvertebrates; Mouth zone; Sediment; Water level